Penerapan Prinsip Desain Kenzo Tange Pada Perancangan Language Education Center - Yuliana Suwito; Yohannes Firzal; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
ASEAN Economic Community (AEC) occurs in Indonesia since 2016. It is necessary for Indonesia to prepare themselves. Besides softskill and knowledge, foreign language ability must be inconcern. To learn foreign language, it needs a proper place, such as Language Education Center. Language Education Center has spaces that its function in accordance with the activities to learntheory, discussion, visual, laboratory, and games that can be used by students. Kenzo Tange design principles are used in this design of the Language Education Center which can support design byexposing the structure and using glass for space separators.The concept applied into this design is Exposed All the Things, which is taken from the vision of this Language Education Center. Thisconcept is applied by exposing what inside the building itself, such as columns, beams, open spaces, using a free-ornament façade, and a simple interior design. This is resulting into a design that canmaximize its function properly.Keywords :Language Education Center, Spaces, Kenzo Tange Principal Design.